Diagnostic Neuroradiology Subspecialty Training: 1 Versus 2 Years; the Canadian Perspective. Issue 4 (November 2021) - Maralani, Pejman Jabehdar; Shewchuk, Jason R.; Joshi, Manish; Ribeiro, Luciana; Carpio-O'Donovan, Raquel del; Landry, David; Sharma, Manas; Zakhari, Nader; Symons, Sean; Morrish, William; Schmidt, Matthias
Background: Canada began a national reform of its post-graduate medical education training programs to a Competence By Design (CBD) model. Trends from accredited neuroradiology programs from the past 10 years were investigated to inform educators and stakeholders for this process. Methods: A 13-question electronic survey was sent to program directors of all 8 accredited neuroradiology training programs in Canada. Data was requested for each year on the 2008-2019 graduating classes. Questions pertained to program enrolment; program completion; post-training employment; and the sufficiency of 1-year training programs. Results: Response rate was 100%. Over the timeframe studied, the 2-year programs increased in size ( P = 0.007), while the 1-year programs remained steady ( P = 0.27). 12.2% of trainees enrolled in the 2-year program dropped out after 1 year, and were considered 1-year trainees thereafter. A higher proportion of 2-year trainees obtain positions within academic institutions (89.5 vs 67.2%, P = 0.0007), whereas a higher proportion of 1-year trainees obtain positions within non-academic institutions (29.3 vs 8.1%, P = 0.0007). A higher proportion of those with Canadian board certification in diagnostic radiology who completed a 2-year program obtained a position within a Canadian academic institution compared to non-certified 2-year trainees ( P < 0.001). 71.4% of program directors agreed that a 1-year program was sufficient for non-academic staff positions. Conclusion: The length of the training program has significant impact on employment in academic vs non-academic institutions. This information can be used to guide the upcoming CBD initiative for neuroradiology programs.